In Search of a New (National) Historical Record – the Republic of Belarus of 1991–1994 - Śleszyński, Wojciech (1970– ) (Institute of History of the Polish Academy of Sciences, 2017)
The final stage of the Soviet Union and the creation in 1991 of a new Belarusian state were characterised by big political whirls. There was the need in a new, post-Soviet reality, for a different look at the nation’s own history. Increasingly strong was national narrative, emphasising the importance of political and national independence. Those milieux demanded that Belarusian sciences should be made independent of the party, for thus far they were treated as the ideological resource base for the communist party.A large part of Belarusians, however, and numerous groups of historians did not see the necessity to break up with Soviet heritage. The majority of citizens of the Belarusian Republic opted for the existence of the Soviet Union as the political entity. A new interpretation of history met neither with any special resistance, nor enthusiasm. It was regarded is as yet another action imposed by the authorities, the only difference being that this time it was possible to criticise it much more easily without the fear of severe reprisals as in the Soviet times.There was a general feeling of nostalgia for the good, Soviet times. The fight for the construction of a new interpretation of history intensified after 1994, when the presidential campaign entered its final stage. Both the national circles and those appealing to the Soviet version of history understood that historical topics made an important element of the campaign which made it possible for electors to better identify with their candidate.An attempt to build a new community based on national banners suffered defeat in the elections of 1994. The society was not ready to reject the Soviet-class system of values and replace it with a new national-Belarusian offered after 1991. Neither a symbiosis was created that could combine these two systems. The “West Russian” idea, developed in the nineteenth century, but modified and Sovieticized during the period of Belarusian Soviet Republic, became a strong element of the Belarusian identity, and national circles proved to be unable to weaken it in the years of 1991–1994.
s. 143-173
Streszcz. ang., ros.
Czasop. kontynuuje numerację wydaw. pt.: Studia z Dziejów ZSRR i Europy Środkowej
Keywords: Białoruś -- 1991- [KABA]; białoruski przekaz historyczny; Idee polityczne -- Białoruś -- 20 w. [KABA]; Rozwój gospodarczy -- aspekt polityczny -- Białoruś -- 1990- [KABA]